Primary Healthcare Efficiency Indicators for Analysis and Decision-Making Support for Managers - Nascimento, Izabel Yale Neves; Santos, Veruska Borges; Pereira, Luis Filipe Alves; Araújo, Tiago Brasileiro; Rocha, Caio Guilherme Moreira da; Medeiros Filho, Fábio Guerra; Andrade, Rodrigo Cardoso Amaral de; Vanderlei, Igor Medeiros; Nascimento Filho, Dimas Cassimiro (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2026: Anais do XXII Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2026.248568, 2026)
Research Context: Efficient management of Brazil’s Primary Healthcare (PHC) is essential to ensure universal access and quality of care, yet challenges in resource allocation and workforce distribution demand innovative solutions for equitable and sustainable delivery. Practical Problem: A key challenge in PHC management is the lack of integrated efficiency metrics across financial, human, and service dimensions, as current static evaluations limit comparative analysis and hinder effective resource allocation. Proposed Solution: By combining financial, human resource, and service delivery data from official sources, we present a set of operational efficiency indicators designed for PHC in Brazil, that enable comparative and dynamic evaluations across units, supporting equitable and evidence-based healthcare management. Related IS Theory: The solution integrates heterogeneous health data into an information system that supports decision-making, aligning automated tools with managerial workflows to improve efficiency in PHC. Research Method: Following an analytic approach, the study evaluates the proposed indicators through a detailed comparison between the Brazilian cities. A quantitative analysis assesses their practical applicability, ensuring the indicators’ effectiveness in supporting decision-making in PHC. Summary of Results: Experiments demonstrate that the proposed solution provides reliable efficiency indicators for PHC units and municipalities. The results highlight disparities in performance and illustrate how these indicators can support data-driven decisions to optimize financial and human resource allocation. Contributions and Impact to IS area: The study contributes to the IS field by proposing efficiency indicators tailored to Brazil’s Primary Health Care and integrating them into a decision-support system, enhancing transparency, comparability, and equity in public sector governance.